Uso da combinação de cetamina e metadona no tratamento da dor neuropática causada por diferentes etiologias clínicas - Godoy, Maria Celoni de Mello de (2013)
Methadone and ketamine have been used in neuropathic pain management, but the benefits of the association of both drugs are uncertain. Aiming to enhance the analgesic efficacy and to reduce the occurrence of adverse-effects, an oral solutionof methadone plus ketamine was tested in patients suffering of neuropathic pain of different etiologies and resistant to other analgesics. All patients were treated in the Clinical Care & Pain Management of Santa Maria University Hospital (HUSM) between October 2006 and March 2008. Pain (primary aim) was analyzed before and several times after starting the treatment, through the visual analogical scale (VAS), allodynia and burning or shooting pain evaluation. The development of adverse-effects (secondary aim), such as somnolence, nausea, vomit, dizziness, hallucination, constipation and headache, was also investigated. The first part of this thesis presented the case report of 18 neuropathic pain patients treated with the oral solution of methadone plus ketamine during 6 months.Except for one patient that discontinued the treatment due to intolerable adverse effect, all patients reported pain relief and lowprevalence of adverse effects throughout the treatment. The second part of this thesis presents arandomized, double-blind study conducted with 37 neuropathic patients. Patients were randomly assigned in three treatment groups: methadone group (n=13), ketamine group (n=11) and methadone plus ketaminegroup (n=13). All patients received the designated treatment by oral route, during 3 months. Methadone, ketamine or methadone plus ketamine treatmentgradually (better effect in 30 than in 7 days) and largely (inhibition of about 70% at the end of treatment) reduced the level of neuropathic pain (VAS) with nodifference between the treatment groups.The proportion of patients presenting burning or shooting pain was similarly reduced in all treatmentgroups, but the prevalence of allodynia was significantly reduced only in ketamine group. Excepted for the somnolence that was more prevalent in methadone and methadone plus ketamine groups, the prevalence of the adverse effects was very similar in all treatment groups. All together, the present data show that the combination of methadone plus ketamine was effective to reliefneuropathic pain resistant to other analgesics, though the combination of the two drugs did not show superior efficacy than those reached by methadone or ketamine alone. This study strengthens the use of methadone or ketamine as alternatives to treat neuropathic pain. The drug of choice, however, should be based on the patient background.